A Responsive Internship Program from the Viewpoint of Beginning Teachers - Boholano, Helen B.; Jamon, Bernard Evangelicom V.; Corpuz, Brenda B.; Bacaltos, Richel N. (Journal International Inspire Education Technology, 2024)
The final semester of a four-year education course involves a student teaching or internship period that poses a number of challenges to cooperating teachers, college supervisors, student teachers, and school administrators, among other stakeholders. This stage connects the theoretical and practical in real-world learning environments, acting as a pillar in the professional development of future educators. A seamless transition from theory to practice is made possible by responsive internship programs that integrate classroom experiences with pre-service training in response to evolving educational demands. This study explores the perspectives and experiences of pre-service teachers in internship programs using a qualitative phenomenological approach. Semi-structured interviews with stakeholders in Visayas, Philippines provide priceless information about program effectiveness and areas for improvement. Important issues come to light, highlighting the need of preparing teacher interns with flexible abilities, incorporating technology, learner-centered approaches, encouraging cooperation between organizations and educational institutions, and professionalism. Experiential learning and exposure to a range of student populations are essential for refining instructional strategies and fostering professional development. The study provides valuable information that may be utilized to improve internship programs, which in turn helps to foster the professional growth of new teachers and improves students’ educational achievement.